Escala de Metacognição - Sênior : evidências de validade, precisão e normas iniciais para idosos - França, Alex Bacadini (2017)
Metacognition can be defined as knowledge and cognition about the cognitive phenomenon, referring to thoughts and knowledge that individuals have about their own thoughts and cognitive processes. Two of its basic elements are: the metacognitive knowledge, which involves consciousness about processes and competencies that are necessary for accomplishing certain tasks; and metacognitive monitoring, which includes judging the effectiveness of strategies and establishing new ones. As such, metacognition plays an important role in the daily life of the elderly, influencing social functions, quality of life and self-efficacy. Prior to this project, a scale to evaluate metacognitive skills was developed, focused on metacognitive knowledge and cognitive monitoring, called the Metacognition Scale-Senior (EMETA-S). Additional studies were needed to demonstrated the validity and improve the EMETA-S. The aim of the studies presented here was to improve the first version of this instrument by means of new analyses of validity based on the internal structure, scale precision and relation with other variables such as gender, schooling and age. The temporal stability of the reformulated scale was also investigated. The model found in the Exploratory Factor Analysis was tested by means of a Factorial Confirmatory Analysis, to verify the adjustment to the theoretical model. In addition, a validity analysis based was conducted on the relationship with an external variable (Mini Mental State Examination) Finally, the initial norms for a scale of schooling and age were elaborated. The EMETA-S was constituted of a single factor of 34 items and presented internal consistency measured by Cronbach's alpha of 0.92. There was a statistically significant difference in scores related to: schooling and age. The correlation between EMETA-S and MEEM was r = 0.43, considered good for instruments measuring related constructs. The results demonstrated that the EMETA-S can be considered a promising tool in the evaluation of the elderly.